Development of Variable Instrument Template for Collecting Dashcam Footage - E.H. Sukadarin; J. Zakaria; M. Widia; N. Mohamed Shah; A.S. Mohd Khairudin (Journal of the Society of Automotive Engineers Malaysia, 2024)
Installing a dashboard camera or dashcam on a vehicle brings many benefits and advantages. The device functions as a closed-circuit CCTV camera to record activities on the road. The rapid development of dashcam technology has inspired researchers to highlight a study that uses dashcam videos to determine road accident status. Based on the researcher’s understanding, many of these accidents happened in the blind spot area of the vehicles. However, conducting the analysis based on the uploaded accident footage is not easy because the downloaded footage is raw and needs to be assessed in terms of quality and validity. Therefore, this study will focus on developing the criteria for analyzing dashcam footage so that the developed template can be used as the minimum variables that need to be focused on to extract information from the accident footage. The existence of dashcam footage has provided researchers the opportunity to investigate actual events when an accident occurred. This scenario offers an opportunity for many parties to understand the causes of the accidents and play a role according to their respective expertise to prevent fatal accidents on the road. It is hoped that with the production of a valid and proven instrument template for analyzing dashcam videos, many researchers will be motivated to do more related studies.